Compensation for a costly ornament depends on the development of flight performance in stalk-eyed flies - Vance, Jason T.; Pehl, Kayla; Acakpo, Comonla J.; Swallow, John G. (Frontiers in Ethology, 2023)
Several species of stalk-eyed flies exhibit exaggerated sexual dimorphism where females favor males with longer eyespans. Longer eyespan increases a fly's moment of inertia, and may, therefore, impact flight behavior and fitness, specifically maneuverability and predator evasion. However, these putative costs may be ameliorated by co-selection for compensatory traits, as flies with longer eyespans tend to have larger thoraces and wings, which allows them to perform turns similar to flies with shorter eyespans. Furthermore, the capacity to compensate for a potentially costly ornament may not be fixed across the life-history of the adult stage, as stalkeyed flies achieve sexual maturity at 3-4 weeks of age, accompanied by significant growth of reproductive tissues and organs. Thus, growth of the abdomen and body mass over time may impose constraints on flight performance that may affect whether an adult reaches the age of reproductive viability. The purpose of this study was to investigate the flight performance of stalk-eyed flies and its relationship to body morphology and development. The flight performance of 1-to-30 day old Teleopsis dalmanni (n=124) and Diasemopsis meigenii (n=83) were assessed by presenting normoxic, variable-density mixtures of heliox (O2, N2 and He) in 10% increments ranging from air to pure heliox; the least-dense gas allowing flight represented maximal performance. Flight kinematics were analyzed using high-speed (5930fps) videography. Immediately following flight assessment, flies were euthanized, photographed, dissected and weighed. In both species, total body mass, thorax and abdominal mass increased across age. Wing kinematics and maximal flight capacity were associated with thorax mass, and increased with age as flies became heavier. Although flies with longer eyespans were indeed heavier, they had larger wings and thoraces; however, maximal flight capacity and kinematics were generally independent of eyespan. Thus, bearing long eye-stalks did not impair flight performance, nor did the increase in mass attributable to reproductive maturation. Instead, variation in flight performance appears associated with the development of the flight motor, and improved ratio of thorax-to-total mass, across age.